Answer:
I think your answer would be A
Step-by-step explanation:
Answer:
![14y + 9](https://tex.z-dn.net/?f=%2014y%20%2B%209%20)
Step-by-step explanation:
Perimeter of the given triangular above = sum of all its sides.
![= (y + 9) + 2y + (4y - 1) = y + 9 + 2y + 4y -1](https://tex.z-dn.net/?f=%20%3D%20%28y%20%2B%209%29%20%2B%202y%20%2B%20%284y%20-%201%29%20%3D%20y%20%2B%209%20%2B%202y%20%2B%204y%20-1%20)
Collect like terms
![= y + 2y + 4y + 9 - 1](https://tex.z-dn.net/?f=%20%3D%20y%20%2B%202y%20%2B%204y%20%2B%209%20-%201%20)
![= 7y + 8](https://tex.z-dn.net/?f=%20%3D%207y%20%2B%208%20)
If Bob creates a new triangle that is 7 less than twice of the perimeter of the triangle above, the expression of the new triangle would be:
![2(7y + 8) - 7](https://tex.z-dn.net/?f=%202%287y%20%2B%208%29%20-%207%20)
Simplify
![2*7y + 2*8 - 7](https://tex.z-dn.net/?f=%202%2A7y%20%2B%202%2A8%20-%207%20)
![14y + 16 - 7](https://tex.z-dn.net/?f=%2014y%20%2B%2016%20-%207%20)
New perimeter = ![14y + 9](https://tex.z-dn.net/?f=%2014y%20%2B%209%20)
Answer:
x=-5
Step-by-step explanation:
Answer:D ( if you add +4 to the (x + 3)^2)
Step-by-step explanation:
Parent function is f(x) = x^2
A translation 3 units left gives y = )x + 3)^2
- and 4 up gives y = (x + 3)^2 + 4 - vertex form.
Standard form :
y = x^2 + 6x + 9 + 4
= x^2 + 6x + 13.